JURIDICAL REVIEW OF HEALTH SERVICE FACILITIES BASED ON LAW NO 17 OF 2023 - Risdawati, Irsyam; Zarzani, T. Riza (International Conference on Health Science, Green Economics, Educational Review and Technology, 2023)
This research is a juridical review of Health Service Facilities based on Law Number 17 of 2023. This study aims to analyze and interpret the legal provisions contained in the law relating to the implementation of health service facilities in Indonesia. The research method used is a normative juridical approach, by examining in depth the text of Law Number 17 of 2023, especially in Articles 165-196 which regulate Health Service Facilities. The analysis is conducted to understand the substance, implications, and scope of these provisions in the practice of health services. The results of this study are expected to provide a deeper understanding of the role of health service facilities in the new legal framework. In addition, this research also aims to identify potential obstacles or problems that may arise in the implementation of the provisions of the law and provide recommendations for future improvements and policy development. This research is expected to contribute to the development of health law, as well as provide a more comprehensive view of the roles and responsibilities of health care facilities in supporting the achievement of national health goals in accordance with applicable regulations